Persepsi Remaja tentang Peran Gender dan Gender Seksualitas di Kota Semarang - Boediarsih, Boediarsih; Shaluhiyah, Zahroh; Mustofa, Syamsulhuda Budi (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTBasically, women and men differ in physical characteristics, however, the difference and a problem when used as an injustice, conflict, suppression and oppression, which raises the existence of injustice and inequality. The aim of research to identify factors that influence adolescent perceptions of gender roles and gender sexuality. Quantitative research with cross sectional approach. A sample of 395 taken by simple random sampling of High School students of class XI in Semarang. Retrieving data using a structured questionnaire. univariate analysis with frequency distribution, bivariate with chi square and multivariate regression logistic. The research showed respondents have a good perception of gender roles and gender sexuality is 51,6% , there is a relationship between the origin of living, sex, peer influence and experience sexuality in dating to the perception of gender roles and gender sexuality in respondents. And sex is the dominant variable contributes.Keywords: adolescence, perception, gender roles, gender sexuality.